Financial Literacy Counseling for Farming Households Toward Climate Change Resilience in Waru Village, Parung District - M. ARIZAL; Khusnul Khatimah (IKRA-ITH ABDIMAS, 2026)
Climate change is a real threat to the long-term viability of farms and the economic stability of farming families, especially in rural Indonesia. This makes farmers even more vulnerable because they can't plan their finances flexibly when they don't know how much they'll make from their harvest. The goal of this community service project is to help farming families become more financially literate. It took place on October 30, 2025, in Waru Village, Parung District, Bogor Regency, and involved 30 members of the PKK of Waru Village. The extension materials taught people how to manage their household income and expenses, keep simple financial records, plan their finances for the seasons, and get to know formal financial institutions. A questionnaire was used to evaluate participants' financial knowledge and access to financial institutions. The results show that 76.6% of participants knew about banks, 60% had savings accounts, and 73.3% knew about more than one type of bank. After the extension, comprehension levels were over 80% of the target set. These results show that using contextual and participatory lecture methods as a first step to help rural farming communities address climate change challenges is an effective way to improve their financial literacy.